Perlindungan Hukum Terhadap Hak Masyarakat Hukum Adat Setelah Berakhirnya Hak Guna Usaha - Urasana, Yules Moses; Laturette, Adonia Ivonne; Radjawane, Pieter (BAMETI Customary Law Review, 2023)
Legal protection of the Ulayat Rights of the Customary Law Community is the highest tenure right of the customary law community covering all lands as well as those belonging to certain environmental areas. The purpose of this study is to discuss the legal protection of the rights of indigenous peoples after the expiration of the HGU. P.T Waitala in West Seram Regency. The type of research used by the author, in this paper, is Normative Juridical legal research, or doctrinal legal research, which is a legal research that uses secondary data sources. This is done by emphasizing and adhering to juridical aspects. Normative legal research is library research, namely research on secondary data. Results of the Research: Legal protection of the Rights of Indigenous Peoples, is a fundamental right that must be owned by customary law communities, which has been stated in the 1945 Constitution of the Republic of Indonesia Article 18b Paragraph (2) states that "The state recognizes and respects legal community units adat has its traditional rights as long as they are still alive and in accordance with the development of society. No. 5 of 1960 concerning Basic Agrarian Principles (hereinafter abbreviated as UUPA) has recognized the existence of Ulayat Rights. Existing recognition is accompanied by 2 (two) conditions, namely by looking at its existence and how it is implemented. Strictly Article 3 UUPA, explains concretely that Ulayat Rights are recognized "as long as in reality they still exist". Therefore, the legal protection of the rights of indigenous and tribal peoples needs to be emphasized in the State.